Maternal Risk Factor Index and Primary Cesarean Delivery among Low-Risk Women in Texas in 2015 [19E]. (May 2018) - Salahuddin, Meliha; Mandell, Dorothy; Lakey, David; Patel, Divya
Abstract : INTRODUCTION: Cesarean delivery (CD) accounts for over one-third of all Texas births (∼400, 000 annually), with primary CD accounting for 20% of the overall CD. We examined associations of maternal risk with primary CD among nulliparous, term, singleton, vertex (NTSV) deliveries in Texas. METHODS: NTSV deliveries to women ages 15-49 years were identified using the 2015 Texas birth file (Center for Health Statistics, Texas Department of State Health Services). A risk factor index was constructed (score range: 0-6), including preexisting diabetes mellitus (DM)/gestational DM (GDM), preexisting hypertension (HTN)/gestational HTN, eclampsia, infertility treatment, smoking during pregnancy, and pre-pregnancy overweight/obesity, and categorized as 0, 1, 2, and 3+ based on the number of risk factors present. Multivariable logistic regression models were conducted to examine the associations between the categorized risk factor index and primary CD, overall and by maternal race/ethnicity. RESULTS: Among the 116, 273 NTSV deliveries, 26.6% had primary CD. The most prevalent risks among those with primary CD were pre-pregnancy overweight/obesity (60.9%), gestational HTN (10.3%), and GDM (5.8%). The adjusted odds for primary CD for 1, 2, and 3+ risk factors were 1.66 (95% CI 1.60-1.71), 2.61 (95% CI 2.48-2.74), and 4.07 (95% CI 3.58-4.62), respectively. This dose-response relationship was observed for all race/ethnic groups. CONCLUSION: Over 50% of NTSV deliveries with primary CD had at least one maternal risk factor. Women with a higher risk index score had elevated odds for primary CD. Understanding patterns of maternal risk associated with primary CD among NTSV deliveries is vital to reducing the overall CD rate in Texas.